[Broadcast Excerpt on Employment Discrimination] (Tufts Archival Research Center, 2007)
Transcript of New York City television news broadcast discussing employment discrimination. Mentions a major Corporation that established a policy restricting its employees from smoking on and off the job. Explains how discrimination based on smoking status is different from age or racial discrimination. Mentions testing employees’ lungs periodically to determine if cigarettes have been smoked.